Inhibition of Rice Serotonin N-Acetyltransferases by MG149 Decreased Melatonin Synthesis in Rice Seedlings - Kyungjin Lee; Geun-Hee Choi; Kyoungwhan Back (Biomolecules, 2021)
We examined the effects of two histone acetyltransferase (HAT) inhibitors on the activity of rice serotonin N-acetyltransferases (SNAT). Two rice recombinant SNAT isoenzymes (SNAT1 and SNAT2) were incubated in the presence of either MG149 or MB3, HAT inhibitors. MG149 significantly inhibited the SNAT enzymes in a dose-dependent manner, especially SNAT1, while SNAT2 was moderately inhibited. By contrast, MB3 had no effect on SNAT1 or SNAT2. The application of 100 μM MG149 to rice seedlings decreased melatonin by 1.6-fold compared to the control, whereas MB3 treatment did not alter the melatonin level. MG149 significantly decreased both melatonin and N-acetylserotonin when rice seedlings were challenged with cadmium, a potent elicitor of melatonin synthesis in rice. Although MG149 inhibited melatonin synthesis in rice seedlings, no melatonin deficiency-induced lamina angle decrease was observed due to the insufficient suppression of SNAT2, which is responsible for the lamina angle decrease in rice.